Ghrelin Protects against the Detrimental Consequences of Porphyromonas gingivalis-Induced Akt Inactivation through S-Nitrosylation on Salivary Mucin Synthesis - Bronislaw L. Slomiany; Amalia Slomiany (International Journal of Inflammation)
Disturbances in nitric oxide synthase isozyme system and the impairment in salivary mucin synthesis are well-recognized features associated with oral mucosal inflammatory responses to periodontopathic bacterium, P. gingivalis. In this study, using rat sublingual gland acinar cells, we report that P. gingivalis LPS-induced impairment in mucin synthesis and associated suppression in Akt kinase activity were accompanied by a decrease in constitutive nitric oxide synthase (cNOS) activity and an induction in inducible nitric oxide synthase (iNOS) expression. The LPS effect on Akt inactivation was manifested in the kinase S-nitrosylation and a decrease in its phosphorylation at Ser473. Further, we demonstrate that a peptide hormone, ghrelin, countered the LPS-induced impairment in mucin synthesis. This effect of ghrelin was reflected in the suppression of iNOS and the increase in Akt activation, associated with the loss in S-nitrosylation and the increase in phosphorylation, as well as cNOS activation through phosphorylation. Our findings suggest that induction in iNOS expression by P. gingivalis-LPS leads to Akt kinase inactivation through S-nitrosylation that detrimentally impacts cNOS activation through phosphorylation as well as mucin synthesis. We also show that the countering effect of ghrelin on P. gingivalis-induced impairment in mucin synthesis is associated with Akt activation through phosphorylation.